Evolutionary exobiology: towards the qualitative assessment of biological potential on exoplanets. Issue 3 (25th October 2017) - Stevenson, David S.; Large, Sean
Abstract: A planet may be defined as habitable if it has an atmosphere and is warm enough to support the existence of liquid water on its surface. Such a world has the basic set of conditions that allow it to develop life similar to ours, which is carbon-based and has water as its universal solvent. While this definition is suitably vague to allow a fairly broad range of possibilities, it does not address the question as to whether any life that does form will become either complex or intelligent. In this paper, we seek to synthesize a qualitative definition of which subset of these 'habitable worlds' might develop more complex and interesting life forms. We identify two key principles in determining the capacity of life to breach certain transitions on route to developing intelligence. The first is the number of potential niches a planet provides. Secondly, the complexity of life will reflect the information density of its environment, which in turn can be approximated by the number of available niches. We seek to use these criteria to begin the process of placing the evolution of terrestrial life in a mathematical framework based on environmental information content. This is currently testable on Earth and will have clear application to the worlds that we are only beginning to discover. Our model links the development of complex life to the physical properties of the planet, something which is currently lacking in all evolutionary theory.